Babak Baru Ketegangan Islam dan Kristen di Indonesia - Husni Mubarok (Studia Islamika, 2014)
Melissa Crouch, Law and Religion in Indonesia: Conflict and the Courts in West Java, (New York: Routledge Contemporary Southeast Asia Series. 2014), xxvi + 214 pages.The effects of Islamization and Christianization have influenced the dynamics of the relationship between Islam and Christianity in Indonesia. For many Muslims, Christianization is perceived as a threat to the future of Indonesian Islam. Christians sense that, especially, the Islamization of public policy, is, likewise, a threat. Law and Religion in Indonesia, written by Melissa Crouch, analyses current data of the relationship between the two largest religions in Indonesia. The book focuses on why tensions between Islam and Christianity—and particularly concerning the issue of Christianization—have emerged as severely as they have since the onset of the democracy period. It analyses how Islamic groups have responded around Christianization. The tensions between the religions have changed with the trend toward the politization of religion. At the same time, the new policy of decentralization has shifted religious-based political competition from the national level to the regions.DOI: 10.15408/sdi.v21i3.1221